Body Mass Index and Long-Term Follow-Up Outcomes in Patients With Acute Myocardial Infarction by the Median of Non-HDL Cholesterol: Results From an Observational Cohort Study in China - Gao, Hui; Shen, Aidong; Chen, Hui; Li, Hongwei (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background: The association between obesity, non-HDL cholesterol, and clinical outcomes in subjects with acute myocardial infarction (AMI) undergoing percutaneous coronary intervention (PCI) is incompletely understood. The aim of this investigation was to explore the association between body mass index (BMI), non-high density lipoprotein (non-HDL) cholesterol, and long-term follow-up prognosis. Methods: This present study used data obtained by the Cardiovascular Center of Beijing Friendship Hospital Database Bank. We identified 3780 consecutive AMI populations aged 25- 93 years from 2013 to 2020. Participants were categorized as normal weight (18.5≤BMI< 22.9 kg/m 2 ), overweight (23.0≤BMI< 24.9 kg/m 2 ), obese class I (25.0≤BMI< 29.9 kg/m 2 ), and obese class II (BMI ≥ 30.0 kg/m 2 ). The endpoint of interest was cardiovascular (CV) death, all-cause death, myocardial infarction (MI), stroke, unplanned revascularization, and cardiac hospitalization. Results: Participants with higher BMI were younger and more likely to be males compared with lower BMI groups. Elevated non-HDL cholesterol was present in 8.7%, 11.0%, 24.3%, and 5.9% of the normal, overweight, obese class I, and obese class II groups, respectively. After multivariate adjustment, compared to normal-weight participants with decreased non-HDL cholesterol (reference group), obese participants with and without elevated non-HDL cholesterol had a lower risk of mortality (with obese class I and elevated non-HDL cholesterol: hazard ratio [HR] 0.44, 95% confidence interval [CI] 0.28-0.67; with obese class I and decreased non-HDL cholesterol: HR 0.68, 95% CI 0.47-0.98; with obese class II and elevated non-HDL cholesterol: HR 0.42, 95% CI 0.20-0.87; with obese class II and decreased non-HDL cholesterol: HR 0.35, 95% CI 0.16-0.72). Conclusion: In AMI participants performing with PCI, obesity had a better long-term prognosis which probably unaffected by the level of non-HDL cholesterol.